Evaluation of financial models from the perspective of capital structure and cash generation: a contribution to management accounting (Journal of Management & Business, 2024)
Companies seek to maximize shareholder value, but this must be balanced with the need to maintain adequate solvency. Capital structure, the mix of debt and equity that a company uses, plays a crucial role in this balance. Finding the optimal capital structure is challenging as it involves weighing risk and profitability. Higher debt can increase the risk of insolvency, but it can also reduce the weighted average cost of capital (WACC) and increase return on investment (ROI). Given the above context, this article aims to analyze the optimal capital structure in companies from the perspective of the impact on cash generation and economic value added (EVA), using a technology company as a case study. A mixed methodology was used, combining deterministic models and probabilistic simulations (Monte Carlo) to evaluate financial performance under different leverage scenarios and capital structures. The results highlight that financial leverage can offer significant advantages in terms of profitability and tax optimization, although it poses challenges in cash flow sustainability. It is concluded that strategic management of installed capacity and careful analysis of financial risk are essential to ensure the balance between profitability and liquidity, contributing to strengthening business decision-making.
Keywords: Capital structure; value maximization; solvency; leverage; cash flows; profitability; risk